Visible light mediated intermolecular [3 + 2] annulation of cyclopropylanilines with alkynes - Nguyen, Theresa H.; Maity, Soumitra; Zheng, Nan (Beilstein Journal of Organic Chemistry, 2014)
Intermolecular [3 + 2] annulation of cyclopropylanilines with alkynes is realized using visible light photoredox catalysis, yielding a variety of cyclic allylic amines in fair to good yields. This method exhibits significant group tolerance particularly with heterocycles. It can also be used to prepare complex heterocycles such as fused indolines.
Keywords: [3 + 2]; alkyne; annulation; cyclopropylaniline; photoredox catalysis; visible light